Exploring the electronic structure and speciation of aqueous and colloidal Pu with high energy resolution XANES and computations. Issue 91 (31st October 2018) - Vitova, Tonya; Pidchenko, Ivan; Fellhauer, David; Pruessmann, Tim; Bahl, Sebastian; Dardenne, Kathy; Yokosawa, Tadahiro; Schimmelpfennig, Bernd; Altmaier, Marcus; Denecke, Melissa; Rothe, Jörg; Geckeis, Horst
Abstract : Pu L3 HR-XANES fingerprints loss of inversion symmetry: rising pre-edge (d, e), shorter A–B distance (d, e), split Pu d-DOS (e). Abstract : Pu L3 HR-XANES and FEFF9 computations provide evidence for band-like 6d states in colloidal Pu contrasting to narrow 6d states in molecular Pu(iv ). Pu L3 HR-XANES is valuable for bond length estimation in plutonyl, whereas Pu M5 HR-XANES is an advanced tool for analysing Pu redox states and 5f unoccupied density of states.